2014
DOI: 10.3171/2014.8.spine131064
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid leakage in Gorham-Stout disease due to dura mater involvement after progression of an osteolytic lesion in the thoracic spine

Abstract: Patients with Gorham-Stout disease (GSD), a rare disease of poorly understood etiopathophysiology, suffer from progressive osteolysis. Destruction of bone matrix is caused by lymphatic vessels, which can lead to CSF leakage if parts of bony structures adjacent to CSF spaces are involved. So far, fewer than 200 patients have been reported in the literature; only 4 of these patients presented with CSF leakage. The authors report the case of a 30-year-old man with GSD and CSF leakage due to dura mater inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Managing chylothorax in GSS includes irradiation therapies, pleurectomy, pleurodesis, thoracic duct ligation and lymphangiomatous tissue excision [2]. Suero et al [18] recommended pleurodesis for intractable pleural effusion. In our case, chest drainage and thoracic duct ligation combined with pleurodesis were performed to relieve the symptoms due to the refractory chylothorax.…”
Section: Discussionmentioning
confidence: 99%
“…Managing chylothorax in GSS includes irradiation therapies, pleurectomy, pleurodesis, thoracic duct ligation and lymphangiomatous tissue excision [2]. Suero et al [18] recommended pleurodesis for intractable pleural effusion. In our case, chest drainage and thoracic duct ligation combined with pleurodesis were performed to relieve the symptoms due to the refractory chylothorax.…”
Section: Discussionmentioning
confidence: 99%
“… 6 To the best of our knowledge, 13 cases of GD of spine have been reported after 2005. 8 20 21 22 23 24 25 26 27 28 29 30 31 A brief review of these cases with treatment and outcome has been shown in Table 2 . Out of the total 41 reported cases of GD of spine, cervical spine is the most commonly affected with 11 cases involving only cervical spine and additional 6 cases involving cervicothoracic spine.…”
Section: Discussionmentioning
confidence: 99%
“…Bony lesions proximate to the dura and surrounding CSF spaces can also result in CSF leaks, manifesting as otorrhea and concomitant meningitis [ 11 ]. In addition, there have been several cases in the literature reporting patients with GSD and CSF leaks with subsequent intracranial hypotension requiring surgical repair [ 3 , 4 , 5 , 6 ], with clinical symptoms to include orthostatic headache, nausea, and vertigo. In 1 of these cases, the authors reported a patient with GSD in whom it was felt that intracranial hypertension was the cause of the patient's subsequent CSF leak [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gorham-Stout disease (GSD), also known as vanishing bone disease, is a rare disorder, which most commonly presents in children and young adults and is characterized by an excessive proliferation of lymphangiomatous tissue within the bones [ 1 ]. This lymphangiomatous proliferation most frequently affects the cranium and axial skeletal bones [ 2 ] and, due to the proximate location to the dura surrounding cerebrospinal fluid (CSF) spaces, can also result in CSF leaks manifesting as intracranial hypotension with clinical symptoms to include orthostatic headache, nausea, and vertigo [ 3 , 4 , 5 , 6 ]. We are presenting the case of a boy with GSD who presented with headaches due to increased intracranial pressure.…”
Section: Introductionmentioning
confidence: 99%